MODERN STATUS AND MODERNIZATION OF THE JAPAN ECONOMY - D. Shevchenko (Вестник университета, 2017)
The article presents an overview of the current state of the Japanese economy substantiates the need to modernize the country's economic development in order to provide competitive advantages in the world market. The evolution of the main macroeconomic indicators of Japan's development is analyzed: public debt, inflation rates, gross domestic product, aggregate supply and demand, exchange rate, etc. The main stages of the development of the Japanese economy have been singled out from the time of the establishment of the market economy to our days.